PROSPECTIV—a pilot trial of a nurse-led psychoeducational intervention delivered in primary care to prostate cancer survivors: study protocol for a randomised controlled trial. Issue 5 (22nd May 2014) - Watson, Eila; Rose, Peter; Frith, Emma; Hamdy, Freddie; Neal, David; Kastner, Christof; Russell, Simon; Walter, Fiona M; Faithfull, Sara; Wolstenholme, Jane; Perera, Rafael; Weller, David; et al.
Abstract : Background: Prostate cancer survivors can experience physical, sexual, psychological and emotional problems, and there is evidence that current follow-up practices fail to meet these men's needs. Studies show that secondary and primary care physicians see a greater role for primary care in delivering follow-up, and that primary care-led follow-up is acceptable to men with prostate cancer. Methods and analysis: A two-phase study with target population being men who are 9–24 months from diagnosis. Phase 1 questionnaire aims to recruit 300 men and measure prostate-related quality of life and unmet needs. Men experiencing problems with urinary, bowel, sexual or hormonal function will be eligible for phase 2, a pilot trial of a primary care nurse-led psychoeducational intervention. Consenting eligible participants will be randomised either to intervention plus usual care, or usual care alone (40 men in each arm). The intervention, based on a self-management approach, underpinned by Bandura's Social Cognitive Theory, will provide advice and support tailored to these men's needs and address any problems they are experiencing. Telephone follow-up will take place at 6 months. Study outcomes will be measured by a questionnaire at 7 months. Phase 1 will allow us to estimate the prevalence of urinary, sexual, bowel and hormone-related problems in prostate cancer survivors and the level of unmet needs. 'Usual care' will also be documented. Phase 2 will provide information on recruitment and retention, acceptability of the intervention/outcome measures, effect sizes of the intervention and cost-effectiveness data, which is required to inform development of a larger, phase 3 randomised controlled trial. The main outcome of interest is change in prostate-cancer-related quality of life. Methodological issues will also be addressed. Ethics and dissemination: Ethics approval has been gained (Oxford REC A 12/SC/0500). Findings will be disseminated in peer-reviewed journals, at conferences, through user networks and relevant clinical groups. Trial registration number: ISRCTN 97242511.